Communion : the female search for love - Hooks, Bell, 1952-2021 (New York : William Morrow/HarperCollins, 2003)
Intimate, revealing, provocative, Communion challenges every woman to courageously claim the search for love as the heroic journey we must all choose to be truly free. In her trademark commanding and lucid language, hooks explores the ways ideas about women and love were changed by the feminist movement, by women's full participation in the workforce, and by the culture of self-help, and reveals how women of all ages can bring love into every aspect of their lives, for all the years of their lives. Communion is the heart-to-heart talk every woman -- mother, daughter, friend, and lover -- needs to have.
Keywords: Vrouwenemancipatie